Penentuan Kondisi Optimum (Konsentrasi HCl dan Konsentrasi Ion Merkuri) pada Ekstraksi Ion Hg2+ Menggunakan Teknik Emulsi Membran Cair - Supriyatno, Tri Octivan; Hamzah, Baharuddin; Said, Irwan (Universitas Tadulako, 2017)
Study on the extraction of mercury ion had been done using emulsion liquid membrane technique. The aim of this study was to determine the optimum condition on mercury ion extraction in solutions those include variations in concentration of HCl solution (0.5 to 2.5) M and variation in concentration of mercury (15-35) ppm.This study was conducted using laboratory experimental method with benzoyl acetone as cation carrier, kerosene as membrane phase, HCl solution as an internal phase, Span-80 and Span-20 as surfactants, and mercury solution as the sample. Determination concentration of mercury ion in external phase was analysed using UV-Vis spectrophotometer. The result showed that the concentration of HCl solution resulted in the optimum percentage of extraction with the percent extraction of 95.31% was at 2 M. In addition, the concentration of mercury solution resulted in percent optimum extraction of 96.58% was at a concentration of 30 ppm.